THE DESIGN OF CHARACTER EDUCATION IN ISLAMIC COLLEGE - Arina Hidayati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Character education in college plays an important role to the state wellbeing. It is because nearly all areas in community need good character. College as one of education institution should organize character education corresponding to the culture and mutually approved strategy. Islamic college with strong Islamic culture should have character education design emphasizing on Islamic values. The embedment of Islamic values into character education can be done through: (1) role modeling, (2) learning implementation, and (3) evaluation on students’ character through applying good character to job practice. Those three programs of character education shouldbe taught sustainably to obtain the optimum result. To design an appropriate character education to Islamic College, the author employed the result of collaborative research conducted on two colleges in Surakarta. This result was expected to be the character education design that could be the example in Islamic colleges in Indonesia.  Keywords: character education, islamic education, islamic character, character education in college.